La Escuela Normal de Logroño : de la creación de un centro docente a la integración social del maestro (1841-1857) - Marie-Hélène B (Universidad de La Rioja, 2013)
The Teacher School of Logroño was one of the first Teacher Schools of Spain, opened between 1841 and 1843. This paper explains the conditions of the creation and the functioning of the teacher education in Logroño and the development of the primary education in the town and the district between 1841 and 1857, from the opening to the Moyano's law. It shows how the studies in Logroño's school were many years ago the natural following of the primary education and the only oportunity for the children of the lowest social classes.